2011
DOI: 10.1111/j.1440-169x.2010.01244.x
|View full text |Cite
|
Sign up to set email alerts
|

Nodal signal is required for morphogenetic movements of epiblast layer in the pre‐streak chick blastoderm

Abstract: During axis formation in amniotes, posterior and lateral epiblast cells in the area pellucida undergo a counterrotating movement along the midline to form primitive streak (Polonaise movements). Using chick blastoderms, we investigated the signaling involved in this cellular movement in epithelial-epiblast. In cultured posterior blastoderm explants from stage X to XI embryos, either Lefty1 or Cerberus-S inhibited initial migration of the explants on chamber slides. In vivo analysis showed that inhibition of No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…It is thought that, in the chicken embryo, the mesoderm is induced by a combination of Wnt and TGF-beta signals coming from a Nieuwkoop centre located in the posterior marginal zone [20, 21]. These mesoderm cells are endowed with different cell behaviours, which are likely to be critical for the execution of these cell flows, since treatments that block mesoderm differentiation also appear to block these cell flow patterns [18, 22]. An interesting but open question is when these rotational movements start, before or during mesoderm differentiation.…”
Section: Mechanisms Driving Epithelial Cell Flow Patterns In the Epibmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that, in the chicken embryo, the mesoderm is induced by a combination of Wnt and TGF-beta signals coming from a Nieuwkoop centre located in the posterior marginal zone [20, 21]. These mesoderm cells are endowed with different cell behaviours, which are likely to be critical for the execution of these cell flows, since treatments that block mesoderm differentiation also appear to block these cell flow patterns [18, 22]. An interesting but open question is when these rotational movements start, before or during mesoderm differentiation.…”
Section: Mechanisms Driving Epithelial Cell Flow Patterns In the Epibmentioning
confidence: 99%
“…Nodal signalling has been implicated in streak formation through its effects on mesoderm differentiation [45]. More recently it has been demonstrated that inhibition of Nodal signalling results in delayed vortex movements and is associated with a reduction in rosette formation, providing further support for a functional link between ingression and streak formation [22, 45]. …”
Section: Mechanisms Driving Epithelial Cell Flow Patterns In the Epibmentioning
confidence: 99%
“…Recently, rosettes have been described during this process. In the epiblast of the chick embryo, rosettes with actin-rich centers are visible within the developing primitive streak (Wagstaff et al, 2008), and rosette number increases as development progresses (Chuai and Weijer, 2008;Wagstaff et al, 2008;Yanagawa et al, 2011). These rosettes are dependent on Nodal signaling, as inhibition of Nodal pathway members results in reduced rosette numbers (Yanagawa et al, 2011).…”
Section: Vertebrate Axis Formationmentioning
confidence: 99%
“…A lack of primitive streak formation in chick embryos overexpressing Nodal antagonists extends the case to birds and the last of the four core vertebrate models, suggesting a pan-vertebral function (Yanagawa et al, 2011).…”
Section: Grns Of Vertebrate Mesoderm Formationmentioning
confidence: 99%